Carbohydrate intake, glycemic load and blood glucose levels of diabetes mellitus patients in Community Health Center of Surakarta City - Farah Hayati Adibah; Siti Zulaekah (Warta LPM, 2022)
Purpose: This study aims to determine the association between carbohydrate intake and glycemic load with fasting blood glucose levels. Methodology: All selected participants filled and signed the informed consent to follow this cross-sectional study. A total of 65 patient with T2DM were selected using a consecutive sampling method. A total of 65 patients with T2DM aged 45 - 69 years old and were active members of PROLANIS who had medical records from the laboratory examination of the latest fasting blood glucose levels. Inclusion criteria such as has no complications illnes and takes antihyperglycemic drugs or insulin injections. Carbohydrate intake and the glycemic load was determined using the Semi-Quantitative Food Frequency Questionnaire form and fasting blood glucose levels by the medical records of the last laboratory examination results. The statistical analysis used was the Rank Spearman test. Results: The results showed 70.8%, 61.54%, and 76.92% of respondents had more carbohydrate intake, high glycemic load consumption, and elevated fasting blood glucose levels, respectively. The results of the study found A significant correlation between carbohydrate intake and glycemic load with fasting blood glucose levels were shown by the value of p = 0.047 and p = 0.002. Application: This research is conducted in Surakarta City at the Community Health Centers of Jayengan, Penumping, Sibela, Pucangsawit, Gajahan, and Manahan.